Evaluation of Serial Urine Viral Cultures for the Diagnosis of Cytomegalovirus Infection in Neonates and Infants. (May 2014) - Chisholm, Karen M.; Aziz, Natali; McDowell, Michal; Guo, Frances P.; Srinivas, Nivedita; Benitz, William E.; Norton, Mary E.; Gutierrez, Kathleen; Folkins, Ann K.; Pinsky, Benjamin A.
Cytomegalovirus (CMV) is the most common cause of congenital infection worldwide. Urine viral culture is the standard for CMV diagnosis in neonates and infants. The objectives of this study were to compare the performance of serial paired rapid shell vial cultures (SVC) and routine viral cultures (RVC), and to determine the optimal number of cultures needed to detect positive cases. From 2001 to 2011, all paired CMV SVC and RVC performed on neonates and infants less than 100 days of age were recorded. Testing episodes were defined as sets of cultures performed within 7 days of one another. A total of 1264 neonates and infants underwent 1478 testing episodes; 68 (5.4%) had at least one episode with a positive CMV culture. In episodes where CMV was detected before day 21 of life, the first specimen was positive in 100% (16/16) of cases. When testing occurred after 21 days of life, the first specimen was positive in 82.7% (43/52) of cases, requiring three cultures to reach 100% detection. The SVC was more prone to assay failure than RVC. Overall, when RVC was compared to SVC, there was 86.0% positive agreement and 99.9% negative agreement. In conclusion, three serial urine samples are necessary for detection of CMV in specimens collected between day of life 22 and 99, while one sample may be sufficient on or before day of life 21. Though SVC was more sensitive than RVC, the risk of SVC failure supports the use of multimodality testing to optimize detection.